Clinical Application of Chinese Herbal Injection for Cancer Care: Evidence-Mapping of the Systematic Reviews, Meta-analyses, and Randomized Controlled Trials - Ming Yang; Si-jia Zhu; Chen Shen; Rui Zhai; Duo-duo Li; Min Fang; Jing-nan Xu; Jing-nan Xu; Ye-na Gan; Lu Yang; Lu Yang; Zhi-ying Ren; et al. (Frontiers Media S.A., 2021)
Background and objective: Cancer is a life-threatening disease worldwide and current standard therapy cannot fulfill all clinical needs. Chinese herbal injections have been widely used for cancer in Chinese and Western hospitals in China. This study aimed to apply evidence mapping in order to provide an overview of the clinical application of Chinese herbal injections in cancer care based on randomized controlled trials, systematic reviews, and meta-analyses.Methods and results: Seven databases were systematically searched for eligible randomized controlled trials, systematic reviews, and meta-analyses for ten Chinese herbal injections used in cancer treatment and covered in the Chinese national essential health insurance program. Excel 2016 and RStudio were used to integrate and process the data.In total 366 randomized controlled trials and 48 systematic reviews and meta-analyses were included in the evidence mapping of herbal medicines including; Compound Kushen, Shenqi Fuzheng, Aidi, Kangai, Kanglaite, Xiaoaiping, Cinobufacin, Brucea javanica oil emulsion, Polyporus polysaccharide injection, and Astragalus polysaccharide for injection. Health insurance restricts the scope of clinical application for these herbal injections. The numbers of studies published increased, especially around 2013-2015. The most studied cancer types were lung cancer (118, 32.2%), colorectal cancer (39, 10.7%), and gastric cancer (39, 10.7%), and the most used injections were Compound Kushen (78, 21.3%), Shenqi Fuzheng (76, 20.8%), and Aidi (63, 17.2%). The most consistently reported benefits were observed for Compound Kushen, Shenqi Fuzheng, Aidi, and Kangai for tumor response, quality of life, myelosuppression, and enhancing immunity.Conclusion: The current evidence mapping provides an overview of the outcomes and effects of Chinese herbal injections used in cancer care, and offers information on their clinical application which warrants further evidence-based research in order to inform clinical and policy decision-making.